The community structure of the mangrove in a selected site at the UP mangrove reserve of Barangay Camaligan, Batan, Aklan. - Salanio, Carilyn Dianco (1999.)
The community structure of mangroves in UP Mangrove Reserve, Barangay Camaligan, Batan, Aklan was studied using a transect plot-line method. Community structure of the mangroves is described in terms of stand basal area, stems per hectare, relative density, relative frequency, relative dominance, importance value, species diversity and evenness index. Physico-chemical parameters like salinity, pH, substrate characteristics, air and water temperature and freshwater source were observed regarding its effect on mangrove distribution., Eight true mangrove species were found in the UP Mangrove Reserve. They were Bruguiera cylindrica, Ceriops decandra and Rhizophora apiculata of family Rhizophoraceae; Avicennia marina and Avicennia rumphiana of family Avicenniaceae: Excoecaria agallocha of family Euphorbiaceae: Lumnitzera littorea and Lumnitzera racemos of family Combretaceae. Bruguiera cylindrica was found to have the highest relative density (68.29%), relative dominance (35.29%) and importance value (204.24). Basal and stand basal area is found to be highest in transect 2, 12899.17 cm squared and 1684.02m squared/ha. respectively. Transect 2 also showed the highest stems per hectare count (36.400 m squared/ha.). The site has a diverse stand as shown by its index of diversity (0.743). It also exhibit low evenness index (0.472) thus has high index of dominance (0.528).
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Mangroves -- Batan Aklan